New Trend in Education after Covid-19 Attack: EFL Higher Students’ Experiences in Hybrid Environment in a Private University - Zidni Ma'ruf (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2023)
After the covid-19 attack for a few years, hybrid environment in education become a new trend in today educational methodology in Indonesia. This is because traditional face to face teaching and learning were forbidden by Indonesian government during covid-19 pandemic. Alternatively, virtual teaching and learning are implemented. The habit of the integration of technology in education continues after the pandemic by implementing hybrid learning and teaching environment. This qualitative research with a case study approach aims to explore EFL higher students’ experiences in hybrid environment. There were six students participated in this research that the researchers got through purposive sampling. Open-ended interview was the main data collection used in this research to give a clear picture and deep understanding of EFL higher students experience in hybrid environment after the pandemic. All the interview data were recorded, transcribed, analyzed, and divided into some themes. Further, member checking was done by the researchers to develop trustworthiness of the research. The findings of this research revealed at least two themes which are the advantages of hybrid environment (free from space-time and increasing speaking ability) and disadvantages of hybrid environment (costly, and bad connection). Further, suggestion and recommendation were offered to all related parties.